A Longitudinal Brain Magnetic Resonance Imaging Study of Neuromyelitis Optica Spectrum Disorder - Kim, Su-Hyun (Public Library of Science, 2014)
Brain involvement is commonly seen in patients with neuromyelitis optica spectrum disorder (NMOSD). However, little is known about the chronic changes of acute brain lesions on MRI over time. Here, our objective was to evaluate how acute brain MRI lesions in NMOSD changed on follow-up MRI. We reviewed the MRIs of 63 patients with NMOSD who had acute brain lesions and follow-up MRI over an interval of at least 3 months. Of the 211 acute brain lesions, 24% of lesions disappeared completely on T2-weighed images (WI) and a decrease in size ≥50% on T2-WI was observed in 58% of lesions on follow-up MRI. However, 47% of lesions revealed focal T1-hypointensity and, in particular, 18% showed focal cystic changes. Cystic changes were observed most commonly in corticospinal tract and corpus callosal lesions whereas the vast majority of lesions in the cerebellum, basal ganglia and temporal white matter resolved completely. MRI remission on T2-WI occurred in 82% of lesions, while approximately half of the lesions presented foci of T1-hypointensity, which may be considered a severe tissue injury over time. The extent of brain injury following an acute brain lesion in NMOSD may depend on the location of the lesion.